Use of PCR to screen for promoter elements in genomic DNA library clones - Poppe, Monika; Paweletz, Neidhard (BioTechniques, 2018)
We report a modified PCR strategy to screen for promoter elements of genes of interest that is based upon consecutive rounds of PCR and appropriate subcloning. Following preliminary identification and sequencing of intron 1 by standardized PCR, the application of a suited cDNA/intron primer combination renders a succeeding PCR-mediated screening of cosmid or P1-derived artificial chromosome (PAC) libraries possible, thus identifying genomic clones comprising the searched promoter elements.We tested our approach in comparison with a commercially available promoter finder kit by searching the promoter elements of the CENP-C gene from the human and mouse genomes. Applying the kit system, we amplified the anticipated promoter from mouse, but failed in isolating human promoter elements. Our approach made use of a 5′-UTR/intron1 primer combination in the second round of PCR, enabling the identification of positive clones from genomic DNA within a human PAC library possible. Subcloning and final PCR amplification revealed the successful isolation of the human promoter.Therefore, we conclude that our approach might represent a helpful alternative to identify promoter elements, especially when prior art genome walking, STS-based strategies or anchored PCR failed.